Central African Republic : Second Review Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Central African Republic's Second Review Under the Extended Credit Facility (ECF) Arrangement. Program implementation as of end-2016 has been broadly satisfactory despite the challenging security situation. All quantitative performance criteria were met while two structural benchmarks were missed. The authorities have adopted strong measures to address customs revenue shortfalls that took place during the first quarter of 2017 and to enhance budget transparency. All three prior actions for the second review were met. The IMF staff supports completion of the second review under the ECF arrangement and the authorities' request for augmentation of access.